BUILD USING NETWORK LAN ROUTER CAN DO TO FULL CONTROL OF ACCESS SERVER - Sutarno Sutarno Sutarno (STMIK Jakarta, 2003)
Local Area Network (LAN) is a network where companies hardware and software coupled to each other can communicate in a particular work area using the data and has a high speed, so that two or more networks can communicate with another network that is located very far in order can perform a full access control from servers to workstations, his workstation as controlling management of a network by using routers.